2022
DOI: 10.2174/1570159x19666210823104916
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dose of Erenumab for Preventive Treatment of Episodic Migraine: A Systematic Review and Meta-Analysis

Abstract: Background : Erenumab is a novel monoclonal calcitonin gene–related peptide receptor antibody that is used for the preventive treatment of migraine. Objectives : To evaluate overall safety and efficacy and dose-response relationship of erenumab in patients with episodic migraine and patients with prior migraine treatment failures. Methods : We searched randomized clinical trials on PUBMED, EMBASE database, and Cochrane Library database. A pair-wise meta-analysis and Bayesian network analysis were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Our conclusions regarding efficacy and safety were mostly consistent with previous meta‐analyses 30,31 . Although our study had several strengths, we also acknowledge some limitations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our conclusions regarding efficacy and safety were mostly consistent with previous meta‐analyses 30,31 . Although our study had several strengths, we also acknowledge some limitations.…”
Section: Discussionsupporting
confidence: 88%
“…Our conclusions regarding efficacy and safety were mostly consistent with previous meta-analyses. 30,31 Although our study had several strengths, we also acknowledge some limitations. First, our study only indicated that erenumab offered a considerable promise of both efficacy and safety advantages over a placebo, but additional horizontal comparisons between erenumab and other CGRP mAbs should be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains unclear whether these previous findings could be directly applicable to headache problems in the specific population of patients [ 26 , 27 ]. An additional limitation of previous studies is that most of them used direct method to compare the effectiveness of this medication class with placebo, unable to show the comparative efficacy of different agents in the lack of direct comparison of different types of CGRP related mAbs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%